Audit committees, External Auditors and Earnings management: Evidence from Chinese non-state-owned enterprises. - Yang, Liuqing (2020)
This paper investigates the effect of the audit committee, external auditors on earnings management in Chinese non-state-owned enterprises to enrich the literature on the influencing factors of earnings management in a different context. Besides, this paper analyses the correlation between the characteristics of the audit committee and earnings management with the aims to provide a theoretical basis for the improvement of the audit committee system. This paper also is intended to offer different perspectives for enterprises to use independent auditors by analysing earnings management from the standpoint of external auditors.